PERAN MASYARAKAT DAN PERMUKIMAN NELAYAN SEBAGAI DASAR PENGEMBANGAN KAWASAN MINAPOLITAN DI LAMONGAN, Studi Kasus Permukiman Minapolis Brondong Lamongan (The Role of Community and Fishing Settlement as a Basis for the Development of the Minapolitan Area i - Rimadewi Suprihardjo; Dian Rahmawati (Tesa Arsitektur, 2014)
The Settlement fishermen is as basic area that contain all the activities of the fishermen in daily life and economic. Moreover, regional development as the settlement Minneapolitan area is using the strategic steps in order to create prosperity of fishermen. Such as: (1) strengthening the local economy and fishery small-scale; (2) strengthening business Secondary Schools As well (UMA); and (3) development of maritime economy and the region, based on fisheries management system. Problems that need to be addressed in any settlement fishermen, is how seamlessly integrates all the potential to improve the economy and the community empowerment. The methods used in this research is using combination approach between rationalistic and naturalistic with the method of qualitative/quantitative exploration. For identifying characteristic coastal settlement in the region, the analysis using adaptation study of Ekistics method that is one of the way to learn more about the settlement scientifically. This research aims to develop the concept settlement Minneapolis, and its role in developing the region Minneapolitan. The process toward development concept settlement Minneapolis, needs to identify the characteristics settlement specifically. This research result can be known the community living characteristic, public life coastal village that has a very important roles in the developing of Minneapolitan region in Lamongan district